The English periodical literature of the Cape Colony from its beginning (1824) to 1835 - Robinson, A M Lewin (African Languages and Literatures, 2023)
A Study of its origin, Development and Character, with special reference to Editors, Publishers and Contributors and its Reflection of the life of the Times